THE IMPACT OF AI ON FUNDAMENTAL HUMAN RIGHTS IN EU COUNTRIES. EXAMINATION OF ACADEMIC STUDIES AND THE POSITIONS OF NON-GOVERNMENTAL ORGANIZATIONS REGARDING THE ETHICAL AND AI LEGAL RISKS - Doina Ljungholm POPESCU; Carmina-Elena TOLBARU (Challenges of the Knowledge Society)
Artificial intelligence (AI) is rapidly changing life in Europe and profoundly transforming contemporary society, influencing multiple aspects of economic, social, and legal life. In the European Union, the development and use of AI pose significant challenges regarding the protection of fundamental human rights, such as the right to privacy, equality, and access to justice. Authorities are implementing strict regulations to ensure that innovation does not compromise essential democratic values, aiming to find a balance where new technologies and the protection of human rights merge in the best interest of humanity. My research aims to analyze the impact of artificial intelligence (AI) technologies on fundamental rights in the EU, identify the risks to these rights, and assess legislative and ethical measures for their protection. The research methodology is based on documentary analysis, meaning the study of European laws and international documents related to AI and human rights. Another method used is comparative evaluation, identifying points of convergence and divergence between the national regulations of member states in implementing EU standards on AI. The research follows a deductive approach, starting with the existing legal framework, such as the Charter of Fundamental Rights of the EU and the General Data Protection Regulation (GDPR), while also considering new initiatives like the Artificial Intelligence Act (AI Act). Additionally, the study examines specialized literature and reports from international institutions, such as the Council of Europe and the European Union Agency for Fundamental Rights. This paper provides a comprehensive analysis of EU regulations on AI and proposes practical solutions to align technology with human rights.